2022
DOI: 10.1177/21650799211039439
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Influence of Physical Work Environment on Office Workers’ Physical Activity Behavior

Abstract: Background Many American workers spend over 7 hours a day at work in primarily sedentary office work. Physical activity is a key aspect of optimizing health and preventing disease; yet, 80% of American adults do not meet the recommended guidelines for physical activity. In this systematic review, the relationship between physical work environment and physical activity among office workers was explored. Methods Of the 321 studies screened, 26 studies met the eligibility criteria and were included for evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…More workplaces should, therefore, implement programs and PA-friendly designs to increase opportunities for incidental movement throughout the workday for their employees. This may be achieved by facilitating the use of stairways and walking-friendly routes inside and outside buildings and by providing sit-stand desks and standing-up areas in meeting/conference rooms [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…More workplaces should, therefore, implement programs and PA-friendly designs to increase opportunities for incidental movement throughout the workday for their employees. This may be achieved by facilitating the use of stairways and walking-friendly routes inside and outside buildings and by providing sit-stand desks and standing-up areas in meeting/conference rooms [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these risks, office workersespecially those with sedentary jobs-engage in relatively little physical activity at work, and this sedentary office culture has been identified as a significant health issue [3]. A systematic literature review demonstrated that designing active office spaces can encourage the increase in physical activity of office workers for their health management [4]. The implementation of active workstations or activity-based flex offices (AFOs) is increasing, and research on the impact of AFOs on productivity, satisfaction, workspace, and health is gaining momentum [5,6].…”
Section: Introduction 1background 11overview Of Active Office Environ...mentioning
confidence: 99%
“…Many successful interventions have addressed multiple levels of influence on behaviours, including at social, ecological, individual, environmental, and policy levels [ 9 , 10 ]. For example, perceptions of manager and colleague support for activity have been associated with reductions in workplace sitting time [ 11 ], and environmental changes such as installing sit–stand desks and active building design have demonstrated benefits for sitting reduction and increased movement [ 12 , 13 , 14 ]. Despite this evidence, workplaces still vary widely in their activity-supportive characteristics, with a study in 230 organisations showing that nearly all had room for improvement [ 15 ].…”
mentioning
confidence: 99%